2015
DOI: 10.1371/journal.pone.0140592
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effect of the CB2 Receptor Agonist JWH-015 in Diet-Induced Obese Mice

Abstract: The cannabinoid receptor 2 (CB2) is well known for its immune modulatory role. However, recent localisation of CB2 receptors in metabolically active tissue suggests that the CB2 receptor plays a significant role in energy homeostasis. This study was designed to investigate the impact of chronic CB2 receptor stimulation on food intake, body weight and mood. Lean male C57BL/6 mice were injected i.p. with the selective CB2 receptor agonist, JWH-015 (0.0, 1.0, 5.0 and 10.0 mg kg-1) to establish dose response param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 73 publications
1
73
1
1
Order By: Relevance
“…CB2 is well known in his immune modulatory eff ect (Cabral and Griffi nTh omas 2009). However, recently it has been found that CB2 plays a role in the energy homeostasis and food intake (Verty et al 2015) (Figure 3).…”
Section: Role Of the Endocannabinoid Systemmentioning
confidence: 99%
“…CB2 is well known in his immune modulatory eff ect (Cabral and Griffi nTh omas 2009). However, recently it has been found that CB2 plays a role in the energy homeostasis and food intake (Verty et al 2015) (Figure 3).…”
Section: Role Of the Endocannabinoid Systemmentioning
confidence: 99%
“…However, although acute ⌬ 9 -THC produces hyperphagic effects in rats (393) and mice (34), chronic administration of the compound does not result in increased body weight. This might be due to 1) the capability of ⌬ 9 -THC to desensitize CB1 receptors, to induce aversive responses, or to act as a partial agonist/antagonist in vivo (212); 2) the different contribution of CB1 on glutamatergic or GABAergic terminals to produce hyperphagic or hypophagic effects, respectively, as shown through the use of conditional CB1 knockout mice lacking CB1 in either population of neurons (55); and 3) the recent finding that CB2 receptor activation instead reduces body weight and fat mass in obese mice (881). Peripheral effects were also described.…”
mentioning
confidence: 99%
“…A common CB2 variant, Q63R, causing reduced CB2 function, has been associated with eating disorders in humans (20). CB2 agonists reduce food intake in lean mice (20) and improve both body weight and obesity-associated inflammation in diet-induced obese mice (21). Moreover, CB2 genetic ablation results in adiposity (22).…”
mentioning
confidence: 99%